Analysis and Investigation of Skew Effect on Behavior and Performance of a Small Scale Three-Phase Self-Excited Induction Generator - Budhapon Sawetsakulanond; Vijit Kinnares (My University, 2011)
This paper presents analysis and investigation of the skew effect on behavior and performance of a three-phase, 220/380V, 8.7/5.0A, Δ/Y connected, 4 poles, 2.2kW self-excited induction generator (SEIG) with different angles rotor skewing. A 2D finite element analysis (2D-FEA) is used to consider core loss, flux density and circuit parameters. Analysis of excitation capacitor values for the SEIG based on a steady-state equivalent circuit model including rotor skew effect is given. Skewed rotor slots with angle of 0° (non-skew), 5° and 10° for the SEIGs are employed. Testing and performance comparisons under steady-state operation with a pure resistive load have been conducted. Obtained results can be guidelines and recommendations for development of effective wind induction generators.
Keywords: Electric Motor Design and Analysis